The mostly cavernicolous millipede genus Stygiiulus Verhoeff, 1929, stat. nov.: taxonomy, distribution and phylogenetic relationships (Diplopoda, Julida, Julidae) - Vagalinski, Boyan; Borissov, Simeon; Bobeva, Aneliya; Canciani, Giacomo; Antić, Dragan Ž. (European Journal of Taxonomy, 2022)
The blind and mostly endogean julid genus Stygiiulus Verhoeff, 1929 stat. nov. is reviewed to include ten species: S. ausugi (Manfredi, 1953) comb. nov., S. fimbriatus (Strasser, 1971) comb. et stat. nov., S. gentianae (Strasser, 1971) comb. et stat. nov., S. illyricus (Verhoeff, 1929) comb. nov., S. insularis (Strasser, 1938) comb. nov., S. maximus (Verhoeff, 1929) comb. nov., S. montellensis (Verhoeff, 1930) comb. nov., S. rotundatus (Strasser, 1962) comb. et stat. nov., S. seewaldi (Strasser, 1967) comb. nov., and S. tobias (Berlese, 1886) comb. nov. The distinctiveness of the genus from Typhloiulus is proven by both morphological and molecular data. The monotypic genus Alpityphlus Strasser, 1967 is here treated as a junior subjective synonym of Stygiiulus syn. nov. Stygiiulus fimbriatus comb. et stat. nov. and S. gentianae comb. et stat. nov., originally described as subspecies of S. ausugi comb. nov., are here erected to full species, while the subspecies S. illyricus stygis (Verhoeff, 1933) comb. et syn. nov. is considered to be a junior subjective synonym of the typical S. illyricus comb. nov. Lectotypes are formally designated for S. gentianae comb. et stat. nov. and S. rotundatus comb. et stat. nov., to stabilize the nomenclature of the two species under Article 74.1 of the ICZN. The phylogeny of the genus, its distribution patterns, and the modified mouthparts in some of its species are discussed.